2018
DOI: 10.1007/s13318-018-0508-4
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Diabetes Mellitus on Glucuronidation and Sulphation of Paracetamol in Patients with Febrile Neutropenia

Abstract: No differences in the pharmacokinetics of APAP, APAP-glu and APAP-sulfate in patients with FN indicates that diabetes does not influence glucuronidation and sulfatation of paracetamol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…DM has other complications, including increased susceptibility to other diseases, loss of mobility with aging, depression, and pregnancy problems (CDC, 2017). The condition can cause pathophysiological changes in the body that include a reduction in gastric emptying time, albumin glycation, and CYP activity; that affect the pharmacokinetics and pharmacodynamics of drugs (Stachowiak et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DM has other complications, including increased susceptibility to other diseases, loss of mobility with aging, depression, and pregnancy problems (CDC, 2017). The condition can cause pathophysiological changes in the body that include a reduction in gastric emptying time, albumin glycation, and CYP activity; that affect the pharmacokinetics and pharmacodynamics of drugs (Stachowiak et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed the influence of diabetes mellitus on the pharmacokinetics of drugs (Stachowiak et al, 2019). Since maintenance of normal blood glucose levels is essential in diabetes monitoring of anti-diabetic drug therapy in the presence of other drugs, the influence of such drugs needs to be evaluated to maintain safety (Kilari et al, 2012).…”
Section: Introductionmentioning
confidence: 99%